Spatio‐Temporal Convergence of Maximum Daily Light‐Use Efficiency Based on Radiation Absorption by Canopy Chlorophyll. Issue 8 (24th April 2018) - Zhang, Yao; Xiao, Xiangming; Wolf, Sebastian; Wu, Jin; Wu, Xiaocui; Gioli, Beniamino; Wohlfahrt, Georg; Cescatti, Alessandro; van der Tol, Christiaan; Zhou, Sha; Gough, Christopher M.; Gentine, Pierre; et al.
Abstract: Light‐use efficiency (LUE), which quantifies the plants' efficiency in utilizing solar radiation for photosynthetic carbon fixation, is an important factor for gross primary production estimation. Here we use satellite‐based solar‐induced chlorophyll fluorescence as a proxy for photosynthetically active radiation absorbed by chlorophyll (APARchl ) and derive an estimation of the fraction of APARchl (fPARchl ) from four remotely sensed vegetation indicators. By comparing maximum LUE estimated at different scales from 127 eddy flux sites, we found that the maximum daily LUE based on PAR absorption by canopy chlorophyll ( ε max chl ), unlike other expressions of LUE, tends to converge across biome types. The photosynthetic seasonality in tropical forests can also be tracked by the change of fPARchl, suggesting the corresponding ε max chl to have less seasonal variation. This spatio‐temporal convergence of LUE derived from fPARchl can be used to build simple but robust gross primary production models and to better constrain process‐based models. Plain Language Summary: Plants absorb light to fix carbon dioxide; the efficiency of this process is termed as light‐use efficiency and can be calculated based on different light absorption definitions. Among the light being absorbed by plants, only a fraction is captured by chlorophyll and can be further used for photosynthesis. In this study, we used satellite data and derived an estimation of the fraction of light that is absorbed by chlorophyll. We found that different plants have a similar efficiency using chlorophyll‐absorbed light to fix carbon dioxide; this efficiency is also found to be stable throughout the season in tropical forest. The results of this study can be used to improve models' capability to estimate the total carbon fixed by plants at global scale. Key Points: EVI and MTCI can be better proxies of fraction of photosynthetically active radiation absorbed by canopy chlorophyll Maximum daily light‐use efficiency for chlorophyll‐absorbed photosynthetically active radiation exhibits less variation across biome types Maximum daily light‐use efficiency for chlorophyll‐absorbed photosynthetically active radiation exhibits less variation across season